The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cem.3436
|View full text |Cite
|
Sign up to set email alerts
|

Data fusion of multiple‐information strategy based on Fourier transform near infrared spectroscopy and Fourier‐transform mid infrared for geographical traceability of Wolfiporia cocos combined with chemometrics

Abstract: Owing to the widespread concern relating to herb safety and quality, there is a momentum to discriminate the geographical traceability of fungus with multiple‐information technologies. In this study, we attempted to evaluate the fusion strategy of multiple‐information for the geographical traceability of this fungus based on Fourier transform near infrared spectroscopy (FT‐NIR) and Fourier‐transform mid infrared spectroscopy (FT‐MIR) with chemometrics. From all results, (1) comparative visualization of t‐distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…When it comes to diagnosing cancer, these numbers are simply too low not to mention that other studies dealing with colorectal cancer data showed a stable higher than 90% accuracy for as the result of classification, albeit with different machine learning methods 41 . Meanwhile, projects revolving around FT‐IR techniques and spectrum level classification via traditional models or modified neural networks managed to reach similar or higher efficiency scores as well 42–47 . However, in some cases, these studies put a lot more focus on the preprocessing of the spectra or even using the different derivatives as input for the machine learning models, which could definitely be a viable option for us to better our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to diagnosing cancer, these numbers are simply too low not to mention that other studies dealing with colorectal cancer data showed a stable higher than 90% accuracy for as the result of classification, albeit with different machine learning methods 41 . Meanwhile, projects revolving around FT‐IR techniques and spectrum level classification via traditional models or modified neural networks managed to reach similar or higher efficiency scores as well 42–47 . However, in some cases, these studies put a lot more focus on the preprocessing of the spectra or even using the different derivatives as input for the machine learning models, which could definitely be a viable option for us to better our results.…”
Section: Resultsmentioning
confidence: 99%
“…41 Meanwhile, projects revolving around FT-IR techniques and spectrum level classification via traditional models or modified neural networks managed to reach similar or higher efficiency scores as well. [42][43][44][45][46][47] However, in some cases, these studies put a lot more focus on the preprocessing of the spectra or even using the different derivatives as input for the machine learning models, which could definitely be a viable option for us to better our results. The accuracy can be improved by adding new slides to the cohort and increasing the number of spectra.…”
Section: Accmentioning
confidence: 99%